Management of Choroidal Neovascularization Associated with Optic Disc Melanocytoma with Intravitreal Aflibercept: A Case Report and Review of the Literature - Hany S. Hamza; Magdy Moussa; Abdelrahman M. Elhusseiny (Case Reports in Ophthalmological Medicine)
Purpose. To report a rare case of melanocytoma associated choroidal neovascularization (CNV) treated with intravitreal aflibercept. Methods. We reviewed the literature for the previous reports and different methods of treatment. Results. Optic disc melanocytoma has been considered as a benign melanocytic tumor that rarely affects vision. There is evidence in the literature of association between choroidal neovascular membrane and disc melanocytoma. Conclusions. In conclusion, our article provides a review of literature of such a rare association in which the ophthalmologists must be aware of its occurrence and possible ways of management.